Manejo da ferrugem em clones de café conilon em sistema de Produção Integrada - Belan, Leônidas Leoni (2012)
The coffee leaf rust (Hemileia vastatrix Berk. et Br) is one of the factors which contributes for the reduction of conilon coffee productivity; and on clones susceptibility, the most important measure of management is done by chemical control. The managem